1957
DOI: 10.1042/bj0670215
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency in the domestic fowl

Abstract: This work was done during the tenure of an Agricultural Research Council Scholarship (F.W.H.) and an I.C.I. Fellowship (J. S. L.). Financial assistance from the Nuffield Foundation is gratefully acknowledged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1959
1959
1991
1991

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…(Tables 6 and 7). Lowe et al (1957) found vitamin E in cat, dog and sheep kidney, the concentration in cat kidney being very high compared with the other two species. The total lipid content of cat kidney is high compared with other species (Mottram, 1916;Turner, 1931 figure (see text).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Tables 6 and 7). Lowe et al (1957) found vitamin E in cat, dog and sheep kidney, the concentration in cat kidney being very high compared with the other two species. The total lipid content of cat kidney is high compared with other species (Mottram, 1916;Turner, 1931 figure (see text).…”
Section: Resultsmentioning
confidence: 99%
“…The unsaponifiable matter was chromatographed on alumina (Brockmann grade 3), as described in previous papers Lowe et al 1957). Grade 0 alumina (P. Spence and Co., Widnes) was partially deactivated with water to Brockmann grade 3, and as a rule 10 g. was taken for each 100 mg. of unsaponifiable matter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However,vitamin . 2 I. BRUCKENTAL, I. ASCARELLI AND A. BONDI I974 response in chicks had also been mentioned by Lowe, Morton, Cunningham & Vernon (1957). The reduction in growth caused by lack of vitamin A indicates the occurrence of marked changes in the rate of protein metabolism.…”
mentioning
confidence: 95%
“…Vitamin A deficiency results in a reduction in comb size, underdeveIoped testes, a decrease in sperm concentration and motility, and an increase in abnormal sperms (Craft, M'Elroy & Penquite, 1926; Burrows & Titus, 1938; Garcia & Paredes, 1957; Lowe, Morton, Cunningham & Vernon, 1957). Adamstone & Card (1934) investigated the effect of a practical-type diet in which vitamin E had been destroyed by ethereal ferric chloride and found that by the end of the 2nd year some birds had become sterile and showed degenerative changes in the testes.…”
Section: Nutrition and Fertility In The Malementioning
confidence: 99%